(untitled) (Fiep Bulletin - online, 2012)
According to a research from 2002, with students of the first semesters of the Physical Education Courses in the city of Curitiba, regarding their expectations of work after having finished the Course, the conclusion which was reached was a limitation of these expectations. A data collection on the labor market regarding working places of the undergraduates, has confirmed the previous research. Due to the big number of Physical Education Courses in Curitiba, it can be pointed that there will be a significant number of professionals in some fields (gyms, sport clubs, schools, etc.) while in other fields (hospitals, senior houses, special schools, etc.) the number of professionals is small. The permanence of the existing ideology in the undergraduate courses in Physical education signalizes in the direction of a lack of sustainability in the profession, graduating professionals into unemployment or instability for the acting professionals. This necessary modification starts in order to achieve a change in the structure of the current curriculums, replacing linear disciplinarily for a system which induces student to the systemic and universal way of thinking in terms of working possibilities.